Second Mesiobuccal Root Canal of Maxillary First Molars in a Brazilian Population in High-Resolution Cone-Beam Computed Tomography - Alves, Claudia Rezende Gomes; Marques, MÃ¡rcia Martins; Moreira, Maria Stella; de Cara, Sueli Patricia Harumi Miyagi; Bueno, Carlos Eduardo Silveira; Lascala, Cesar Ã‚ngelo (Iranian Endodontic Journal, 2019)
Introduction: The second canal of the mesiobuccal root (MB2) of the maxillary first molars (MFM) is difficult to detect in conventional radiographs and can be a major cause of failure in endodontic treatments. The aim of this study was to investigate the prevalence and anatomy of the MB2 by using high-resolution cone-beam computed tomography (CBCT). Methods and Materials: Three radiologists examined 414 high-resolution CBCTs. Of these, the CBCTs of 287 patients (mean age 49.43±16.76) who had at least one MFM were selected, making a total of 362 teeth. Prevalence and its relation with gender and age of the patients, side of the tooth, and Vertucci’s classification were analyzed. Data were statistically analyzed (P<0.05). Results: A total of 68.23% of the teeth exhibited the MB2. The presence of the MB2 was equivalent in both genders and significantly higher in younger patients. There was no correlation between the presence of the MB2 in relation to both the sides of the MFM and the FOV size. Smaller FOV recognized higher Vertucci’s grades. Conclusions: It was concluded that the prevalence of the MB2 canal in maxillary first molars in this Brazilian population examined with high-resolution CBTCs is 68.23%, being more prevalent in young patients. Gender and the side examined are no factors for determining the presence of MB2. Although the both FOVs of the high-resolution CBTCs (FOV 8 and 5) detect the MB2 canal, smaller FOV (FOV 5) is more accurate in the analysis of the internal anatomy of such root canals, according to the Vertucci´s classification. Keywords: Cone-beam Computed Tomography; High Resolution; Maxillary First Molar ; Mesiobuccal Root; High Resolution